If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -1y = 110 Solving X + -1y = 110 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add 'y' to each side of the equation. X + -1y + y = 110 + y Combine like terms: -1y + y = 0 X + 0 = 110 + y X = 110 + y Simplifying X = 110 + y
| 7x-3x(x+1)= | | 6+2[3j-2]=4[1+j] | | 1/y-1/2=4 | | 6(z/2-5)=36 | | q=10000-125p | | 12x^2-121/12=0 | | 12=m/5 | | X+y=280 | | 5.5=-1.5+x | | 2.3+n+1.4=0 | | x-86=135 | | -2(-5v+5)=5[2v+3(v+1)] | | Y=x^2-10x+45 | | 3(4x-3)+8x=68 | | 14xy-4xy=o | | -7=-17+x | | -5n-5(-7-2n)= | | E=0.14x^2+7.8x+540 | | -10(t-6)+116-16=108 | | 5x^9/8-15=0 | | 3600+x^2+144=x^2 | | 4(3x-2)/7=4 | | 178w=-1114 | | 2x-6=116 | | x-(-14)=34 | | 3x-2+2=6+2 | | 5-(b+3)=-1+2(b-3) | | 13-(8x)+4x-(-12)= | | x^2+25x-300=0 | | 5x+2(5x-15)=60 | | -6v=-16v+30 | | 10-16x=-230 |